On the feasibility of producing Lu-177 in the IEA-R1 reactor via the direct route (Brazilian Journal of Radiation Sciences, 2021)
Over the last years the 177Lu radioisotope has attracted great interest for the use in therapeutic and diagnostic procedures simultaneously, being what is now called a theranostic radioisotope. There are mainly two ways of producing this radioisotope, by direct neutron capture in a 176Lu target (the “direct route") or by irradiating a 176Yb sample, producing 177Yb that will then decay to 177Lu (also referred as the “indirect route”). In this work the feasibility of producing 177Lu in the IEA-R1 nuclear reactor via the direct route was assessed, and the specific activity that could be obtained was estimated both experimentally and theoretically, allowing for a discussion on the feasibility of commercially producing 177Lu by 176Lu neutron capture in the IEA-R1 reactor.